(untitled) - Lưu, Nguyễn Quốc Hưng (Cần Thơ, 2007)
There are 07 units of 15 lessons. The course is theme-based and the grading is progressive. That is, the later units are more difficult than earlier ones but units and parts of units can be used independently of each other. This means that teachers can select those units and activities that they consider most appropriate for their students, and that if students miss the occasional lesson they will not "lose the thread" of the course as a wole.
Keywords: English languages